Rhodotorula mucilaginosa: A source of heterogeneous catalyst for biodiesel production from yeast single cell oil and waste cooking oil. (November 2020) - Gohain, Minakshi; Bardhan, Pritam; Laskar, Khairujjaman; Sarmah, Saswati; Mandal, Manabendra; Bora, Utpal; Chandra Kalita, Mohan; Goud, Vaibhav Vasant; Deka, Dhanapati
Abstract: Biodiesel obtained from yeast derived single cell oil (SCO) is considered as an alternative to conventional biodiesel derived from plant oils, having the potential to substitute petroleum-derived transport fuels. In this work, we have developed a heterogeneous potassium hydroxide catalyst (K-RAC) supported on Rhodotorula mucilaginosa deoiled cake activated carbon (RAC) to enhance the conversion of R. mucilaginosa isolate R2 derived SCO as well as waste cooking oil (WCO) to biodiesel. The prepared catalyst was characterized by XRD, FTIR, EDX, SEM, BET and TGA. Basicity of the catalyst was determined by CO2 -TPD and the hammet indicator test. The maximum fatty acid methyl esters (FAME) conversion of 96.6% and 98.66% for SCO and WCO respectively were obtained at optimized parameters i.e. 9:1 molar ratio (methanol/oil), 3 wt % of K-RAC loading at 60 °C and reaction time of 3 h. 1 H NMR and GCMS was used to confirm the formation of biodiesel. The K-RAC was recycled effectively for five consecutive cycles. Graphical abstract: Image 1 Highlights: Rhodotorula mucilaginosa ) deoiled cake was used as a potential catalyst (K-RAC) for transesterification reaction. K-RAC was characterized by various techniques. Basic sites (K2 O) on K-RAC facilitated biodiesel production from yeast single seed oil (SCO) and waste cooking oil (WCO). FAME conversion of 96.6% and 98.66% for SCO and WCO was achieved with 3 wt % K-RAC. The catalyst could be recycled for five successive cycles.